Survival outcomes and prognosis predictors of uveal melanoma from Indian population - Payal N Shah; Mahesh Shanmugam; Neha M Kagathi; Annu T Thaliath; Sunita Mohan (Indian Journal of Ophthalmology)
Purpose: Choroidal melanoma is an uncommon malignancy in the Asian Indian population, with limited survival data available for this demographic. This study aims to evaluate the survival outcomes and prognostic factors in a cohort of Asian Indian patients with choroidal and ciliochoroidal melanoma. Methods: We conducted a retrospective analysis of 150 patients with choroidal and ciliochoroidal melanoma between 2011 and 2023 at a single tertiary eyecare and ocular oncology center in India. The demographic and clinical profile, using Collaborative Ocular Melanoma Study (COMS) and American Joint Committee on Cancer (AJCC) classification and histopathological features, were recorded. Patients were contacted through various avenues such as telephone, email, and other social media to know their survival status. Kaplan–Meier survival curves and Cox regression were used to determine survival probabilities and prognostic factors. Results: Of the 150 patients, nearly half (48%) of the patients were 50 years or younger at presentation. The melanoma metastasis-related mortality was 16%. The five-year survival was more than 90% in stages T1 and T2, 80% in stage T3, while it dropped to almost 65% in stage T4. The five year disease specific survival (DSS) was 84% (95% CI: 77%–90%), and the 10 year DSS was 66% (95% CI: 53%–77%). Multivariate Cox proportional hazards analysis revealed a significantly increased risk of disease-specific mortality with higher tumor stage, i.e., T2: hazard ratio (HR) = 1.78 (95% confidence interval [CI]: 1.01–3.13; P = 0.045), T3: HR = 4.24 (95% CI: 2.35–7.64; P < 0.001) and T4: HR = 6.38 (95% CI: 3.21–12.67; P < 0.001), compared to T1. Overall, 29 patients developed metastasis during the study period. The five-year metastasis rate was 16% (i.e., 83% of metastasis occurring within first five years), and 10-year metastasis rate was 19.3%. Conclusion: This study highlights favorable survival outcomes in Indian patients with choroidal melanoma, despite a younger age at presentation. The critical window for metastasis management is within the first five years, underscoring the necessity of structured follow-up protocols.